Effect of practicing soccer juggling with different sized balls upon performance, retention, and transfer to ball reception - Raastad, O.; Aune, T. K.; van den Tillaar, R. (Motor control, 2016)
The aim of this study was to investigate if making the skill acquisition phase more difficult or easier would enhance performance in soccer juggling, and if this practice has a positive intertask transfer effect to ball reception performance. Twenty-two adolescent soccer players were tested in juggling a soccer ball and in the control of an approaching ball at a pre, post and retention test. The participants were randomly divided in a small ball size and bigger ball size training group that both trained four times per week for 6 weeks. At the post and retention test both groups enhanced performance in soccer juggling test with no difference between groups and no increase in ball reception performance at these tests. It was concluded that about intra task transfer and retention of soccer juggling skills, it does not matter if you increase (small balls) or decrease the difficulty (larger balls) when using the same amount of practice time within the skill acquisition phase in soccer juggling. In addition that for ball juggling and ball reception (inter task) these two tasks differ too much in afferent information and movement characteristics that no positive transfer between these two skills no positive intertask transfer can be expected. ABSTRACT FROM AUTHOR